Financial Feasibility Study for Utilizing Flue Gas Emissions from the Adipala Power Plant to Generate 5 kW of Electricity - Hermawan, Rendi Hendra Eka; Prabowo, Eri (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
Electric power reliability remains central to Indonesia’s economic stability while decarbonization pressures increase. This study evaluates the technical and economic feasibility of recovering flue-gas heat from the Adipala coal-fired power plant to generate 5 kW via a micro Organic Rankine Cycle (ORC). Field measurements at the economizer duct show a flue-gas mass flow of 55,000 kg h⁻¹ at 170 °C, corresponding to about 400 kW_th of recoverable heat. A thermodynamic model with realistic parasitic losses and a 12% cycle efficiency indicates a net electrical output of 5 kW with exhaust temperature maintained at 110 °C and boiler backpressure limited to 2 mbar, so boiler operation is not disturbed. Economic appraisal uses a discounted cash-flow model with CAPEX USD 15,000, annual O&M USD 450, availability factor 0.80, electricity price USD 0.10 kWh⁻¹, and discount rate 10%. Results show annual net cash inflow USD 3,054, NPV ≈ USD 11,000, IRR ≈ 19.8%, BCR = 1.59, and a simple payback of ~4.9 years. Sensitivity checks indicate project resilience to reasonable variations in availability, carbon pricing, and component cost. The findings demonstrate that small-scale ORC deployment on plant economizers can be technically sound, economically attractive, and supportive of modest emissions reduction and asset-management goals for thermal power stations.